Acute myeloid leukemia therapy elicits durable complete response in chemoradio‐resistant metastatic paraganglioma. Issue 5 (2nd November 2016) - Sait, Sameer; Kobos, Rachel; LaQuaglia, Michael P.; Pandit‐Taskar, Neeta; Modak, Shakeel
Abstract: Few effective therapeutic options exist for patients with metastatic paraganglioma (PGL). We report the case of a 16‐year‐old male who developed acute myeloid leukemia (AML) 30 months following the treatment for metastatic PGL. PGL had been refractory to 131 I‐meta‐iodobenzylguanidine and temozolomide therapy. However, there was a major reduction in primary tumor allowing its gross total resection, and complete resolution of metastatic disease following AML‐directed therapy that included daunorubicin, cytarabine, and etoposide. He remains in remission for both AML and PGL, 48 months post AML chemotherapy. Alternative chemotherapeutic agents should be considered for metastatic PGL resistant to conventional therapy.